2014
DOI: 10.1111/vec.12155
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of different temperature reading techniques and associated stress response in hospitalized dogs

Abstract: Objective -To evaluate the accuracy and associated induced stress response of axillary, auricular, and rectal thermometry in hospitalized dogs. Design -Prospective observational study from October 2011 to February 2012. Setting -University veterinary teaching hospital. Animals -Two hundred fifty hospitalized dogs. All hospitalized dogs were considered eligible unless their condition precluded measurement at one of the designated sites. Interventions -A veterinary auricular infrared device for auricular tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 27 publications
(46 reference statements)
5
69
0
1
Order By: Relevance
“…This study has shown that healthy dogs completing short periods of routine exercise in the UK can reach a RT of 40°C, highlighting the potential risks facing dogs exercising over longer periods during the warmer spring and summer months. Gomart et al, (2014) suggested using correction factors to improve the reliability of the TMT when compared to RT, but did not report how significant these improvements were. This required using three different correction factors ranging from +0.2°C to +0.6°C determined by gender and coat type.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study has shown that healthy dogs completing short periods of routine exercise in the UK can reach a RT of 40°C, highlighting the potential risks facing dogs exercising over longer periods during the warmer spring and summer months. Gomart et al, (2014) suggested using correction factors to improve the reliability of the TMT when compared to RT, but did not report how significant these improvements were. This required using three different correction factors ranging from +0.2°C to +0.6°C determined by gender and coat type.…”
Section: Discussionmentioning
confidence: 99%
“…This variation may be due to the use of nonveterinary specific auricular thermometers. The veterinary specific devices appear to be more reliable with mean differences ranging from -0.015 °C to 0.77 °C (Rexroat et al, 1999;Gonzalez et al, 2002;Wiedemann et al, 2006;Greer et al, 2007;Piccione et al, 2011;Lamb et al, 2013;Gomart et al, 2014;Smith et al, 2015). The majority of these studies report that TMT measures consistently lower than rectal temperature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study performed at the same institution, axillary temperature (AT) appeared to be correlated with and was less stressful than RT recording in dogs (Gomart and others 2014). However, all measures in that study were performed by a single observer.…”
Section: Introductionmentioning
confidence: 94%